Use of Nursing Support Among Nurses for Caregiver Burden in Family Caregivers of Terminally Ill Patients with Cancer in Palliative Care Units in Japan: Multisite Cross-Sectional Study - Kohei Kajiwara; Masamitsu Kobayashi; Kimiko Nakano; Yusuke Kanno; Miharu Morikawa; Yoshinobu Matsuda; Jun Kako (Palliative Medicine Reports)
Purpose: This study explores the use of nursing support among nurses for caregiver burden in family caregivers of terminally ill patients with cancer in palliative care units (PCUs). Methods: Requests were sent to 389 institutions, and cooperation was received from 162 PCUs. Nurses at 162 PCUs were asked to participate in an Internet survey regarding nursing practices for caregiver burden in Japan. The frequency of six nursing support practices (extracted in a scoping review) was reported using a 5-point Likert scale. Results: The response rate was 22.3% (539/2448). Support for reducing caregiver stress was the most frequently provided nursing support (mean Likert score: 2.41 for monthly prognosis and 2.42 for weekly prognosis). Psychological and educational support was mainly provided via non-face-to-face (telephone) (mean Likert score: 2.26 for monthly prognosis and 2.21 for weekly prognosis) and face-to-face methods (mean Likert score: 2.32 for monthly prognosis and 2.29 for weekly prognosis). Conclusion: Nursing support was provided through telephone support and face-to-face interactions and aimed at reducing caregiver stress among nurses and family caregivers of patients with terminal cancer in PCUs. In this study, the trends in nursing support were similar for patients with a prognosis of weeks or months.